1999
DOI: 10.1212/wnl.52.3.498
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic findings and prognosis of chronic inflammatory demyelinating polyneuropathy

Abstract: Axonal loss is the major long-term pejorative prognostic factor in CIDP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
184
3
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(203 citation statements)
references
References 33 publications
13
184
3
3
Order By: Relevance
“…9 The sural nerve which is commonly biopsied is a distal sensory nerve which is not usually affected in the pathologic process. 10,11 The brunt of nerve dysfunction falls on the motor fibres, nerve roots and proximal trunk. The extent of autonomic nervous involvement could not be ascertained as we lack diagnostic facilities to do so.…”
Section: Discussionmentioning
confidence: 99%
“…9 The sural nerve which is commonly biopsied is a distal sensory nerve which is not usually affected in the pathologic process. 10,11 The brunt of nerve dysfunction falls on the motor fibres, nerve roots and proximal trunk. The extent of autonomic nervous involvement could not be ascertained as we lack diagnostic facilities to do so.…”
Section: Discussionmentioning
confidence: 99%
“…autoimmune pathologies in a variety of experimental models (Munz et al, 2009) and have been reported to be temporally associated with the development of neurological deficits in CIDP patients (McCombe et al, 1987) (Bouchard et al, 1999). Due to their ability to cause persistent infections that periodically reactivate, human herpesviruses such as the alpha-herpesvirus herpes simplex virus (HSV), the beta-herpesvirus cytomegalovirus (HCMV) and the gamma-herpesvirus Epstein-Barr virus (EBV) are candidate triggers of autoimmune diseases development and exacerbation.…”
Section: Infectious Pathogens and Antiviral Immune Responses Triggermentioning
confidence: 99%
“…, 1999 ; Harbo, Andersen, Jakobsen, 2008; Said, 2006). Although the main pathology in CIDP is segmental demyelination, several studies demonstrated coexistence of axonal degeneration following segmental demyelination termed secondary axonal degeneration (Bouchard et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although the main pathology in CIDP is segmental demyelination, several studies demonstrated coexistence of axonal degeneration following segmental demyelination termed secondary axonal degeneration (Bouchard et al. , 1999; Boukhris et al. , 2004 ; Said, 2006; Sghirlanzoni et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation